Performance efficiency of Employees in a Food industry in Nakhon pathom province. - Trichan et al., Praewpan (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
The objectives of this research were to 1) study the organization’s internal environmental factors and the performance efficiency of employees in a food industry in Nakhon Pathom Province, 2) compare the performance efficiency of employees in a food industry in Nakhon Pathom Province by personal factors, and 3) study the relationship between the organization's internal environment factors and the performance efficiency of employees in a food industry in Nakhon Pathom Province. The populations used in this research were 560 employees from a food industry in Nakhon Pathom Province and the samples used in research were 234 employees using Stratified Samplings. The instrument used to collect data was the questionnaire, which content and questionnaire validity have been evaluated. Moreover, the data were analyzed using Percentage, Mean, S.D., T-test, One-Way Anova, Correlation coefficient analysis, and content analysis. The results of the study were; 1. The organization's internal environment factors were found at a high level, when considering at each aspect can be found that the results were in high level. The performance efficiency of employees were found at a high level, when considering at each aspect can be found that work quality and work quantity were at the highest level and time at a high level. 2. The comparison of the performance efficiency by personal factors had no difference of employees who differ in genders in overall and each aspect, however, the employees who differ in age, educational level, monthly income, and work experience had significantly different performance efficiency differently at the level of 0.05 as well as the hypothesis. 3. For the relationship between the organization's internal environment and the performance efficiency, the internal environment factors in the management system were associated with performance efficiency and job quality was found at the highest level. (r=0.74**) Article history: Received 17 August 2020 Revised 12 September 2020 Accepted 14 September 2020 SIMILARITY INDEX = 1.49 %